2009
DOI: 10.1007/s11136-009-9463-5
|View full text |Cite
|
Sign up to set email alerts
|

Replenishing a computerized adaptive test of patient-reported daily activity functioning

Abstract: Purpose Computerized adaptive testing (CAT) item banks may need to be updated, but before new items can be added, they must be linked to the previous CAT. The purpose of this study was to evaluate 41 pretest items prior to including them into an operational CAT. Methods We recruited 6,882 patients with spine, lower extremity, upper extremity, and nonorthopedic impairments who received outpatient rehabilitation in one of 147 clinics across 13 states of the USA. Forty-one new Daily Activity (DA) items were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Although the AM-PAC is comprised of three domains; Mobility, Daily Activities, and Applied Cognition, 15,16 only the 132 item Mobility item bank 17,18 was utilized in this study. 12,13 Each item queries respondents regarding the amount of difficulty they experience performing a specific activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the AM-PAC is comprised of three domains; Mobility, Daily Activities, and Applied Cognition, 15,16 only the 132 item Mobility item bank 17,18 was utilized in this study. 12,13 Each item queries respondents regarding the amount of difficulty they experience performing a specific activity.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 The scale ranges from 0 (none) to 10 (as bad as it can be). 23,2420,2119,20 Participants were asked to rate their “worst pain,” fatigue, and dyspnea over the past seven days preceding each assessment point.…”
Section: Methodsmentioning
confidence: 99%
“…6 is formed. There are studies that found GRM shows better fit with data (Baker, Rounds, & Zevon, 2000;Demirtaşlı, Yalçın, & Ayan, 2016;Gardner et al, 2004) as well as GPCM (Aybek, 2016a;Haley et al, 2009;Walter et al, 2007). Researchers should investigate to find out which IRT model is applicable most to their data.…”
Section: Graded Response Model (Grm)mentioning
confidence: 99%
“…31,32 Item response theory/CAT methods allow the addition of new items into calibrated banks with replenishment calibrations studies. 33 CAT systems currently in use include the Patient Reported Outcomes Measurement Information System 34 and the osteoarthritis (OA) CAT systems ie OA-DISABILITY-CAT, OA-FUNCTION-CAT). 35,36 Both instruments address pain and function, but neither tool focused specifically on younger persons with FAI during initial development.…”
Section: Future Directions: Computer-adaptive Testing Systemsmentioning
confidence: 99%